Estrategias de marketing digital en la promoción turística de la Provincia Los Ríos - Ortiz Lastra, Shirley Magdalena (2020)
Innovations and modern management methods encourage territories to be treated as products. The set of marketing strategies adapted to the current digital era, is called digital marketing and is indispensable in the management of products and tourist destinations. Through this case study, emphasis is placed on the analysis of promotional strategies focused on tourist activity in the province of Los Ríos. For this purpose, a specific methodology was carried out, focusing on online searches of the websites of the cantons of study, as well as the tool of surveys for convenience. This research work is a pioneer in showing the digital marketing strategies carried out in the Province of Los Rios. It is expected that the results of this work will have both business and social implications. Being useful to apply new strategies in the territories and thus promote better and greater tourism development in them.